#TITLE_ALTERNATIVE# - SIANIPAR (NIM S2-888606), MANGASI
An attempt has been made, through a series of laboratory tests, to determine the feasibility of inserting sand columns into the foundation soil as a means of ground improvement in Jakarta clay. Consolidation tests were performed on models 60 mm high having a sand column installed at the centre of each specimen at selected sand densities, termed as maximum, medium and minimum and for various column diameters (15 mm, 20 mm and 25 mm). The diameter of each specimen, the sequence and the magnitude of load applied to each test specimen were as in the standard procedure for consolidation testing. The laboratory model tests indicated that the insertion of sand columns into soil, taken from a location close to the plannned centre line of the Jakarta Outer Ring Road, West Link section, could be effective in reducing settlement. The inclusion of the centre sand columns showed that the rate of radial drainage, expressed in terms of Cvr, was greater than the rate of vertical drainage, expressed in terms of Cv, sometimes significantly. The undrained shear strength of the Jakarta clay was found to correspond with the results of Jakarta soils reported elsewhere.